2020
DOI: 10.1111/pin.12977
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profiling of multiple primary cancers including synchronous lung adenocarcinoma and bilateral malignant mesotheliomas: Identification of a novel BAP1 germline variant

Abstract: We report a case with a rare combination of synchronous lung adenocarcinoma and bilateral malignant pleural mesotheliomas in a 70-year-old male without asbestos exposure. He metachronously developed peritoneal malignant mesothelioma, intrahepatic cholangiocarcinoma, urothelial carcinoma of the bladder and prostatic adenocarcinoma. Immunohistochemistry revealed complete loss of BAP1 expression in all seven lesions. Targeted next generation sequencing using Todai OncoPanel identified a novel germline variant (c.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Although BAP1 loss is not often detected in LUAD [40], we did not detect BAP1 protein expression by IHC analysis. Our results shows that LUAD may be associated with BAP1-TPDS, as previously reported [29].…”
Section: Family Pd-578supporting
confidence: 91%
See 1 more Smart Citation
“…Although BAP1 loss is not often detected in LUAD [40], we did not detect BAP1 protein expression by IHC analysis. Our results shows that LUAD may be associated with BAP1-TPDS, as previously reported [29].…”
Section: Family Pd-578supporting
confidence: 91%
“…Although the tumor genome of sporadic mesothelioma patients has been extensively investigated, the tumor genome of patients affected by BAP1 -TPDS has yet to be systematically characterized. A single paper analyzed the genome of several metachronous tumors in a BAP1 -TPDS patient [ 29 ]. In a recent study involving 17,152 patients with different tumor types, Srinivasan et al reported some information of the somatic genome of six patients with TPDS [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…3. There is no extrathoracic metastasis [22,23] . In our study, we found no signs of metastasis on any PET/CT images, including lymph node metastasis and organ metastasis.…”
Section: Discussionmentioning
confidence: 94%
“…3. There is no extrathoracic metastasis ( 17 , 18 ). In our study, we found no signs of metastasis on any PET/CT images, including lymph node metastasis and organ metastasis.…”
Section: Discussionmentioning
confidence: 99%